Pelatihan Manajemen Bencana Dengan Table Top Disaster Simulation: Perintisan Desa Siaga Bencana di Kabupaten Musi Rawas Sumatera Selatan: Disaster Management Training Using Table Top Disaster Simulation: a Disaster Preparedness Village Pioneer in Musi Rawas Regency, South Sumatra - Susmini, Susmini; Wijaya, Sapondra; Soewito, Bambang; Wibowo, Wahyu Dwi Ari; Dahliana, Dahliana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Minimizing the impact that occurs due to disasters, and preparing for the possibility of a disaster occurring is the most important thing that must be done, including preparing human resources to be ready to face the disaster itself. One form of preparing society to be able to respond well to disasters is by providing good education and training on how to respond to disasters. Table Top Disaster Simulation is an effective education and training method for preparing human resources. This activity aims to increase community knowledge about disaster management as part of the Disaster Preparedness Village pilot in Air Satan Village, Musi Rawas Regency, South Sumatra. This activity is community service using education and training methods with a total of 33 participants. Participants' disaster management knowledge was measured before and after attending education and training using a questionnaire. The evaluation results showed that there was an increase in knowledge before being given the training with the average knowledge score of participants being 44.71, while after being given the training the average knowledge score was 78.32. After conducting education and training using tabletop disaster simulation, public knowledge about disaster management increased. It is hoped that after this pioneering disaster preparedness village activity, education and training will continue to be carried out on other factors in responding to disasters such as training on handling injuries for lay people, training on handling drowning victims for lay people, and so on.